Modulation of poly-N-acetylglucosamine accumulation within mature Staphylococcus epidermidis biofilms grown in excess glucose - Cerca, Filipe (2011)
PNAG is a major component of Staphylococcus epidermidis biofilms involved in intercellular adhesion as well as in the interaction of the biofilm with components of the host immune response. Synthesis of PNAG has been found to be regulated by several environmental factors. In the present study, the effect of glucose metabolism-dependent culture medium acidification in PNAG accumulation was evaluated. Established S. epidermidis biofilms were allowed to grow in excess glucose with or without maintained pH conditions. PNAG accumulation in these biofilms was determined by flow cytometry and fluorescence microscopy using wheat germ agglutinin as a fluorescent probe. Biofilms grown in maintained pH conditions presented significantly higher amounts of this polymer as well as higher icaA expression than biofilms grown in acidic pH conditions. Moreover, PNAG accumulation in biofilms grown in non-maintained pH conditions occurred in association with cell death. Overall, we show that glucose metabolism by decreasing the culture pH affects biofilm physiology in respect to PNAG production and cell death. The reported in vitro modulation of PNAG accumulation within S. epidermidis biofilms further highlights the role of environment on determining the biofilm physiological state.